PENGARUH PERSEPSI NILAI, PERSEPSI MEREK DAN PERSEPSI HARGA TERHADAP MINAT BERKUNJUNG (Studi Kasus pada Pariwisata Alam Omah Kayu di Batu) - Dewi Fitriani; Rois Arifin; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTNature tourism is a from of tourism activities that utilize the potential ofnatural resources and environmental order. Natural tourism omah wood is atourism that has a concept of tourism made of wood that is founded on pine treesthat grow on the slopes of many mountains. Beautiful scenery that can be enjoyedin natural attractions omah wood is the main attraction for visitors to stay or thetourists who come just to take pictures. Because of the interest of visiting can leadto public perceptions about nature tourism. The problem formulation in thisresearch is how influence of perception of value, brand perception and priceperception to the interest of visiting the tourists who exist in natural tourism omahwood. The purpose of this study is to know and analyze how the influenceperseption value, brand perception and price perceptions of visiting interest innatural tourism omah wood. Population in this study is the visitors of naturaltourism wooden urban stone. Samples taken in this study as many as 2000samples with the method of purposive sampling. Data type used is primary data.This type of research is hypothesis testing research. Using multiple linearmethods. The conclusion of this study is the variable of perception of value have asignificant effect on the interest of visiting. Variable perseption brandsignificantly influence the interest of visiting, variable perception of price have asignificant effect on the interest of visiting. The variables of perception of value,brand perception and price perception simultaneously have a significant effect oninterest in visiting.Keywords : Value Perception, Brand Perception, Price Perception,VisitingInterest, Multiple Linear Regression.